Application of Arrhenius kinetics on MHD radiative Von Kármán Casson nanofluid flow occurring in a Darcy-Forchheimer porous medium in the presence of an adjustable heat source. (14th October 2021) - Ragupathi, P.; Muhammad, Taseer; Islam, Saeed; Wakif, Abderrahim
Abstract: This research paper explores the implications of nonlinear Rosseland thermal radiation and temperature-dependent heat generation on non-Darcian steady MHD convective Casson nanofluid flows over a radially extended rotating disk. Besides, the significance of the activation energy is also taken into account in the present modeling during the chemical reaction process. Based on the boundary layer theory, the associated dimensionless boundary layer equations are derived mathematically in the context of Von Kármán's proposition. By invoking a trustworthy BVP4C numerical algorithm, the nonlinear differential system defining the resulting boundary value problem is handled successfully with the help of an iterative shooting procedure, whose results are profiled graphically and tabularly versus the varying values of the pertinent flow parameters. Furthermore, the displayed findings show that the radial and azimuthal nanofluid motion slows down significantly with the strengthening in the Casson nanofluid parameter, the Forchheimer number, the porosity parameter, and the magnetic parameter. However, the stretching parameter exhibits a dual dynamical tendency. A thermal enrichment can be provided by intensifying the heat generation parameter, the temperature difference parameter, the thermal radiation parameter, the thermophoresis process, and the Brownian motion of nanoparticles. On the other hand, it is perceived a remarkable boosting up in the concentration profile with the higher estimation in the thermophoresis and activation energy parameters.